Late Infantile Neuronal Ceroid Lipofuscinosis: Two Case Reports (Bangladesh Journal of Child Health, 2024)
Neuronal ceroid lipofuscinoses (NCLs) are a group of lysosomal storage disorders characterized by progressive, neurodegenerative course. NCLs are classified into four subtypes according to age of onset. Among them, late infantile variety is the second most common condition. Patients typically manifest with seizures, cognitive, motor deterioration and vision loss. Here, we reports two cases of NCLs, because of rarity of this disease in such a young age. As the disease advanced, patients experienced repeated episodes of seizures, ataxia, gradual deterioration of vision and loss of ambulation and speech. The electroencephalogram showed focal epileptiform discharges over left central and parietal region. Magnetic resonance imaging of Brain revealed extensive cerebral and cerebellar atrophy. A skin biopsy extracted from the armpit area displayed periodic acid-schiff (PAS) stained eosinophilic intracytoplasmic inclusions (curvilinear like). These findings are compatible with neuronal ceroid lipofuscinoses. Genetic testing for NCL is the gold standard investigation but patient can also be diagnosed by clinical correlation and positive histopathology findings in low income countries.Bangladesh J Child Health 2023; Vol 47 (2) : 113-116